Receptarea cinematografică a operei Olhăi Kobylianska. - Нікоряк, Наталія (București : Institutul Cultural Român, 2025)
The article emphasizes the need to supplement the literary discourse with the thematical issue of the intermediary poetics, namely the film reception of the biography and works of Olha Kobylianska. It is noted that the cinematography had an organic impact on the life and works of the Bukovinian author. This is evidenced by her autobiographies, biographical studies, as well as the works written under the impression of the cinematography (“By Situations”), or which imply the cinema code in the plot (“The Black Apostle”), or those that demonstrate a pronounced cinematic poetics (“The Ghost”, “The Battle”). The poetry and prose of the author are mentioned to become an integral part of the cinematographic discourse, that is traditionally activated in relation to writers on the eve of their anniversary. The analyzed documentaries “The Valse Brillante. Olha Kobylianska” (2013) and “To be one’s own goal. Olha Kobylianska” (2014) present a receptive version of her biography, created in a productive collaboration of the filmmakers and the literary critics. The functional potential of the biographical films, that popularize and actualize the works of this outstanding personality, contribute to the full understanding of Olha Kobylianska as a complete artistic phenomenon. Emphasis is placed on the fact that compared to biographical projects, film reception of the writer’s works is significantly more productive, which contributes to the reconstruction of a holistic perception of her literary heritage. The films “Earth” (1954), “The Wolfhound” (1967), “The Melancholic Waltz” - “Valse mélancholique,” (1990), “The Princess” (1994), “Nature. The Third Film” (television series “The Island of Love” 1995–1996), “On Sunday Morning She Gathered Herbs” (2019) are the film texts of different genres that demonstrate the occasional attention to the works by Kobylianska in the cinematic environment, due to a certain historical situation, another anniversary or the desire of filmmakers to re-interpret the classical works.